Academic views on Peace Talk Promotion in the Southern Border Provinces - mukem, abdunrohman (Journal of Human Rights and Peace Studies, 2024)
This research article aims to understand the views of academics in support of peace talks in the Southern border provinces through in-depth interviews and field notes from 9 Thai researchers on the conflict and its resolution. This research, conducted from 1 May to 30 September 2020 involved 4 outsiders in, 2 insiders in, 2 insiders out, and 1 outsider out. A typology and taxonomy of the collected data, is followed by analysis, description, and explanation of the findings.Research Finding: an environment conducive for peace talks represents an initial step towards achieving peace. Experts advise 7 critical strategies for effective action, including attentive listening to all people's comments, cultivating a positive narrative through peace-oriented information, fostering unity across diverse faiths, conducting unbiased and sincere conflict resolution efforts, supporting civil society and ensuring freedom of peace-promoting spaces, refraining from undue interference with the Southern Border Provinces Administrative Centre, and avoiding stereotyping and unjust arrests. 7 ongoing strategies are: enhancing the quality of life for the populace, advancing the dualistic educational system, serving